2017
DOI: 10.19126/suje.335497
|View full text |Cite
|
Sign up to set email alerts
|

“Güneş Sistemi ve Ötesi: Uzay Bilmecesi” Öğretmenler Bu Üniteyi Nasıl İşliyor?

Abstract: Öz. Fen bilimleri dersinin konularını yaşamın kendisi oluşturmaktadır. Bu konuların içerisinde hareket, madde gibi basit gözlemlerle deneyimleyebileceğimiz konular olduğu gibi atom, hücre, uzay gibi doğrudan gözlemleme imkânı olmayan konular da yer almaktadır. Dolayısıyla öğrencilerin bu konulardaki kavramları doğru yapılandırabilmeleri için öğretmenlerin buna yönelik hazırlıklar yaparak dersleri işlemeleri gerekmektedir. 7. sınıf konusu olan "Güneş Sistemi ve Ötesi" ünitesi de görsellerle ve materyallerle des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…It was also found that a significant number of teachers preferred the resources prepared by private publications and the digital contents of these resources in addition to the textbook, some of them prepared the digital contents themselves, and some of them used social media environments. In the literature, it is seen that the most preferred digital resource of teachers is EBA (Aydınözü et al, 2016;Geçici, 2022;Yılmaz & Laçin Şimşek, 2017). It can be said that one of the most important reasons for this situation is controllability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was also found that a significant number of teachers preferred the resources prepared by private publications and the digital contents of these resources in addition to the textbook, some of them prepared the digital contents themselves, and some of them used social media environments. In the literature, it is seen that the most preferred digital resource of teachers is EBA (Aydınözü et al, 2016;Geçici, 2022;Yılmaz & Laçin Şimşek, 2017). It can be said that one of the most important reasons for this situation is controllability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Oysa bu konu alanında da öğrenciyi aktif kılacak yöntem ve tekniklerin etkin bir şekilde kullanılması mümkündür (Bakırcı, Artun ve Şenel, 2016;Çepni ve Şenel Çoruhlu, 2014;Deniş Çelikel ve Balım, 2012;Çavuş, Kulak, Berk ve Öztuna Kaplan, 2011). Öğretmenlerin bu öğrenme alanını belirtmemiş olmaları, bu konularda öğrenci merkezli etkinliklerin yapılmasının zor olduğunu düşünmeleri veya bu konunun 2017 fen bilimleri dersi öğretim programına kadar en son konu alanı olarak yer alması nedeniyle ihmal edilmesinden (Yılmaz ve Laçin Şimşek, 2017) kaynaklanabilir.…”
Section: Tartışma Ve Sonuçunclassified